The effect of strontium ranelate on the healing of a fractured ulna with bone gap in rabbit. Issue 1 (December 2016) - Ibrahim, Mohd; Singh, Simmrat; Merican, Azhar; Raghavendran, Hanumantha; Murali, Malliga; Naveen, Sangeetha; Kamarul, Tunku
Abstract Background Fracture healing in bone gap is one of the major challenges encountered in Orthopedic Surgery. At present, the treatment includes bone graft, employing either internal or external fixation which has a significant impact on the patient, family and even society. New drugs are emerging in the markets such as anabolic bone-forming agents including teriparatide and strontium ranelate to stimulate bone growth. Based on the mechanism of their actions, we embarked on a study on the healing of a fractured ulna with bone gap in a rabbit model. We segregated ten rabbits into two groups: five rabbits in the test group and five rabbits in the control group. We created a 5 mm bone gap in the ulna bone, removing the periosteum as well. Rabbits in the test group received 450 mg/kg of strontium ranelate via oral administration, daily, for six weeks. The x-rays, CT scans and blood tests were performed every two weeks. At the end of six weeks, the rabbits were sacrificed, and the radius and ulna bones harvested for histopathological examination. Results Based on the x-rays and CT scans, fracture healing or bone formation was observed to be faster in the control group. From the x-ray findings, 80 % of the fracture united and by CT scan, 60 % of the fracture united in the control group at the end of the six-week study. None of the fractures united in the test group. However, the histopathology report showed that a callus of different stages was being formed in both groups, consisting of 80 % of bone. The serum levels of osteocalcin and alkaline phosphatase initially remained similar up to three weeks and changed slightly at the end of six weeks. Conclusions We conclude that the strontium effect begins slowly, and while it may not interfere with bone cell proliferation it may interfere in the mineralization and delay the acute stage of fracture healing. We recommend that a larger sample size and a longer duration of the study period be implemented to confirm our finding.